FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI RISIKO PRODUKSI USAHATANI JAGUNG (Zea mays sp.) DI DESA WONOREJO KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG - Rosidatul Annisa; Bambang Siswadi; Farida Syakir (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
AbstractThe purpose of this research are analyze the factors that affect the production of farming corn production and socio-economic factors that affect the risk of farming corn production. This research was determined by purposive in Wonorejo Village, Sumbergempol District, Tulungagung Regency. In this research, sampling is determined by Slovin method, and we use 35 sample of corn farmer from Wonorejo village. The analytical method which used in this research is Cobb-Douglass, Production Variance and Multiple Linear Regression. The factors that influence the usahatani corn production are labor and urea fertiliser. The results of regression analysis of production risk using the Varience production method can be concluded that the factors that influence the risk of farming corn production are seeds, labor, urea fertilizers, ZA fertilizers, and NPK mutiara fertilizers. Socio-economic factors that influence the risk of corn production are age, education and income.Keyword: Risk of Production, Socio-economic, Corn